Engineering the Yeast Yarrowia lipolytica for Production of Polylactic Acid Homopolymer - Lajus, Sophie; Dusséaux, Simon; Verbeke, Jonathan; Rigouin, Coraline; Guo, Zhongpeng; Fatarova, Maria; Bellvert, Floriant; Borsenberger, Vinciane; Bressy, Mélusine; Nicaud, Jean-Marc; Marty, Alain; Bordes, Florence (Frontiers in Bioengineering and Biotechnology, 2020)
Polylactic acid is a plastic polymer widely used in different applications from printing filaments for 3D printer to mulching films in agriculture, packaging materials, etc. Here, we report the production of poly-D-lactic acid (PDLA) in an engineered yeast strain of Yarrowia lipolytica. Firstly, the pathway for lactic acid consumption in this yeast was identified and interrupted. Then, the heterologous pathway for PDLA production, which contains a propionyl-CoA transferase (PCT) converting lactic acid into lactyl-CoA, and an evolved polyhydroxyalkanoic acid (PHA) synthase polymerizing lactyl-CoA, was introduced into the engineered strain. Among the different PCT proteins that were expressed in Y. lipolytica, the Clostridium propionicum PCT exhibited the highest efficiency in conversion of D-lactic acid to D-lactyl-CoA. We further evaluated the lactyl-CoA and PDLA productions by expressing this PCT and a variant of Pseudomonas aeruginosa PHA synthase at different subcellular localizations. The best PDLA production was obtained by expressing the PCT in the cytosol and the variant of PHA synthase in peroxisome. PDLA homopolymer accumulation in the cell reached 26 mg/g-DCW, and the molecular weights of the polymer (Mw = 50.5×103 g/mol and Mn = 12.5×103 g/mol) were among the highest reported for an in vivo production.